2016
DOI: 10.18632/oncotarget.9860
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution in relapsed and refractory diffuse large B-cell lymphoma is characterized by high dynamics of subclones

Abstract: Little information is available about the role of certain mutations for clonal evolution and the clinical outcome during relapse in diffuse large B-cell lymphoma (DLBCL). Therefore, we analyzed formalin-fixed-paraffin-embedded tumor samples from first diagnosis, relapsed or refractory disease from 28 patients using next-generation sequencing of the exons of 104 coding genes. Non-synonymous mutations were present in 74 of the 104 genes tested. Primary tumor samples showed a median of 8 non-synonymous mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…It was first demonstrated in solid and other hematologic malignancies [70][71][72][73] that the founding clone of the relapse specimen can be detected at a minor prevalence at the time of initial diagnosis ( Figure 3B). In the context of lymphoma, several studies have observed similar patterns in DLBCL and FL [29,35,42]. In a study of 15 tFL patients, the majority of patients (87%) Relapse/refractory genomics in B-cell lymphomas 605 present in the primary specimens.…”
Section: Progression Through Expansion Of Rare Clones Versus Persistementioning
confidence: 88%
See 2 more Smart Citations
“…It was first demonstrated in solid and other hematologic malignancies [70][71][72][73] that the founding clone of the relapse specimen can be detected at a minor prevalence at the time of initial diagnosis ( Figure 3B). In the context of lymphoma, several studies have observed similar patterns in DLBCL and FL [29,35,42]. In a study of 15 tFL patients, the majority of patients (87%) Relapse/refractory genomics in B-cell lymphomas 605 present in the primary specimens.…”
Section: Progression Through Expansion Of Rare Clones Versus Persistementioning
confidence: 88%
“…These results suggest that TP53 mutations may confer resistance to R‐CHOP therapy. Moreover, two studies with matched primary/relapse DLBCL specimens reported the acquisition of a TP53 mutation at relapse , with deep‐sequencing analysis demonstrating the existence of the mutation at a minor prevalence in in the primary specimen . These results suggest that clones harboring TP53 mutations may be selected for.…”
Section: Recurrent Molecular Themes Associated With Lymphoma Disease mentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, treatment with a targeted therapy in the context of a clinical trial after second line of salvage tended to influence the outcome in our cohort. A recent biological study showed that clonal evolution analysis at the time of refractoriness might explain the differential outcomes and chemosensitivity that have been observed in these populations . Other biological studies are warranted to identify at the time of diagnosis those primary refractory patients in order to propose different treatment strategies (ie, targeted strategies) that should be evaluated in a context of a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there are only a few of such studies and the overall number of cases analyzed is limited. 10 , 11 , 21 , 71 In the alternative approach, unpaired relapsed/refractory tumors are analyzed and frequencies of detected genetic alterations are compared to the respective frequencies in independent primary tumor collectives. This approach allows analysis of larger cohorts, but it has a significant drawback in that it is nearly impossible to accurately differentiate between mutations present at the primary stage and those that are relapse-specific.…”
Section: Genetic Events Related To (Clonally-related) Recurrencesmentioning
confidence: 99%